1992
DOI: 10.1002/1097-0142(19920801)70:3<709::aid-cncr2820700328>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and postoperative cytokines in patients with cancer

Abstract: Background. Changes in tumor necrosis factor‐alpha (TNF‐α), interleukin‐1 alpha (IL‐1α), interleukin‐1 beta (IL‐1β), interleukin‐6 (IL‐6), and granulocyte macrophage‐colony‐stimulating factor (GM‐CSF) were investigated before and after operation in patients with hepatocellular carcinoma (HCC), metastatic liver carcinoma, and gastrointestinal carcinoma. Results. Serum levels of TNF‐α, IL‐1α, and IL‐1β were high in patients with liver carcinoma (HCC and metastatic liver carcinoma) before operation in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 12 publications
1
44
0
3
Order By: Relevance
“…It is worth mentioning that the measurement of cytokine serum level should be performed not less than 2 or 3 months after treatment because surgery or chemotherapy typically increases cytokine serum levels (particularly proinflammatory or proangiogenic). [61][62][63] We have also observed this phenomenon in our study (data not shown).…”
Section: Cytokine Serum Levels During Follow-upsupporting
confidence: 82%
“…It is worth mentioning that the measurement of cytokine serum level should be performed not less than 2 or 3 months after treatment because surgery or chemotherapy typically increases cytokine serum levels (particularly proinflammatory or proangiogenic). [61][62][63] We have also observed this phenomenon in our study (data not shown).…”
Section: Cytokine Serum Levels During Follow-upsupporting
confidence: 82%
“…TNF-␣ has been reported to be closely involved in the pathogenesis of chronic liver disease. 22,32,33 Released by infiltrating lymphocytes, TNF-␣ can trigger both pro-survival and pro-apoptosis signaling through the NF-B pathway and the caspase8 pathway. The cell fate determination mainly depends on the balance between these two pathways.…”
Section: Discussionmentioning
confidence: 99%
“…22 TNF-␣ is closely involved in the induction of apoptosis and in triggering destruction of liver. 23 To test whether EphrinA2 exerts a similar resistant effect in this cytokineinduced apoptosis, we performed TNF-␣ treatment on both control and EphrinA2-overexpressing cells.…”
Section: Ephrina2 Is Up-regulated In Established Cellmentioning
confidence: 99%
“…Tumour cell membrane vesicles were found to induce the release of macrophage TNF-oa (Hasday et al, 1990). This may explain that high plasma concentrations of inflammatory cytokines and blood mononuclear cell cytokine mRNA levels, in particular of TNF-a, were found in gastrointestinal cancer patients (Balkwill et al, 1987;Nakazaki, 1991). Moreover, in situ hybridisation studies of samples obtained from colon cancer patients have identified TNF-a-producing cells as belonging to the macrophage lineage, whereas IL-13 and IL-6 were less frequently detected (Beissert et al, 1989;Naylor et al, 1990).…”
mentioning
confidence: 99%